Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Garis Singgung Lingkaran Pada Pembelajaran Matematika Siswa Kelas VIII SMP Muhammadiyah 5 Surakarta - Isnawati, Nur; , Dr. Sumardi, M.Si (2017)
This research was conducted with the aim of describing the difficulties and knowing the factors causing students to have difficulty in solving the tangent problem of the circle. This type of research is descriptive skin. The subjects of this study were 29 students from grade VIII B in SMP Muhammadiyah 5 Surakarta. Data collection techniques in this study using test methods, observation, and interviews. Data validity is done by triangulation method, by comparing test result data with interview. Data analysis technique is done by three stages: data reduction, data presentation, and data verification and conclusion. The analytical framework was developed based on the category of difficulty. The research results obtained three types of difficulty that is difficulty understanding the concept, difficulty how to paint, and difficulty calculation. Factors causing the difficulty in general that students can not understand the purpose of the problem because it does not master the basic concept of tangent circle. And the level of understanding and creativity of students is low in identifying real problems into the mathematical model. Keywords: difficulty, solve the problem, tangent to the circle.